The use of aunque in peninsular Spanish: A discursive-functional analysis - Olbertz, Hella; Garcia, Talita Storti [UNESP]; Parra, Beatriz Goaveia Garcia [UNESP] (GN1 Sistemas e Publicacoes, 2016)
In this study we describe the use of aunque in Spanish narrative texts. We use Functional Discourse Grammar as a descriptive tool, without however going into technical details. The conjunction aunque is used for the expression of concessive and concessive conditional meanings, which can, globally, be distinguished through the use of the indicative in the former and that of the subjunctive in the latter case. In concessive sentences, aunque can modify descriptive or interactional apodoses. In the first case, the concessive clause acts as an adverbial modifier of either events or propositions, whereas in the second, the concessive clause modifies either a discourse act or a larger communicative entity, the so-called move. In conditional concessive contexts, the aunque protasis is of a scalar nature and can express real or unreal conditions. In addition to modifying eventive and propositional apodoses, the concessive conditional clause can express hypothetical minimal properties of events.
El Uso De Aunque En El Español Peninsular: Un Análisis Discursivofuncional
Keywords: Concessive conditional sentences; Concessive sentences; Conjunction aunque; Functional Discourse Grammar